2004
DOI: 10.1094/cchem.2004.81.4.444
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Storage of Freshly Harvested Paddy Rice on Milled White Rice Flavor

Abstract: Between harvest and the start of drying, paddy rice may be held for more than 24 hr at moisture contents ranging from 16% to >26%. Microbes found on the freshly harvested rice grow under these conditions and produce a wide variety of volatile compounds that impact the flavor/aroma of the white rice obtained after drying and milling of the paddy rice. The contents of 10 volatile microbial metabolites were compared in white rice obtained from paddy rice harvested at differing moisture contents and immediately dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…The other second best variety from Brazil, BRS Jaçanã, only differed from BR IRGA-417 (also harvested in 2008) by having a lower level of sour/silage (Table 4). Sour/silage is an off-flavor note that increases with increase in harvest moisture content of paddy and length of storage prior to drying (Champagne et al 2004a) and, thus, was not inherently higher in BR IRGA-417.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other second best variety from Brazil, BRS Jaçanã, only differed from BR IRGA-417 (also harvested in 2008) by having a lower level of sour/silage (Table 4). Sour/silage is an off-flavor note that increases with increase in harvest moisture content of paddy and length of storage prior to drying (Champagne et al 2004a) and, thus, was not inherently higher in BR IRGA-417.…”
Section: Resultsmentioning
confidence: 99%
“…The technique has been used extensively for determining the effect of different growing and/or processing conditions on sensory properties of rice (Champagne et al 1997(Champagne et al , 2004a(Champagne et al , b, 2007(Champagne et al , 2009Meullenet et al 1999Meullenet et al , 2000.…”
Section: Introductionmentioning
confidence: 99%
“…This technique was introduced in studies on the flavor indicators of rice (Grimm et al, 2001(Grimm et al, , 2004Wongpornchai et al, 2004). Champagne et al (2004Champagne et al ( , 2005 investigated the volatile microbial metabolites gathered in rice based on the SPME technique. Laguerre et al (2007) reported the rapid evaluation of rice aroma by analysis of the volatile fraction using SPME directly coupled with mass spectrometry (MS).…”
Section: Introductionmentioning
confidence: 99%
“…However, the solvent extraction method is timeconsuming, as it requires many steps in sample preparation and, thus, is not appropriate when a large number of the limited amount of rice samples is to be analyzed. Champagne et al investigated the volatile microbial metabolites gathered in rice based on the solid phase micro-extraction (SPME) technique [11,12]. Moreover, Laguerre et al reported the rapid evaluation of rice aroma by analysis of the volatile fraction using SPME directly coupled with mass spectrometry (MS) [13].…”
Section: Introductionmentioning
confidence: 99%